Bug tracking and project management system application in an electronic design company - Fatih Yücalar; Sadık Arslan (Pamukkale University Journal of Engineering Sciences, 2016)
In this study, commercially available Bug Tracking and Management Information Systems has been investigated in a comprehensive manner. The systems that commonly used described in detail. Bug Tracking and Project Management Systems requirements analysis of medium-sized companies and Kentkart Ege Electronic which is an Information Technology company has been made. Obtained by the analysis requirements, the appropriate tools are selected for system application. JIRA that a product of Atlassian company was determined as a Bug Tracking and Project Management application tool. In this study, JIRA system adapted to the requirements, Bug Tracking and Project Management systems is designed in a structure which can be easily used by R&D employees. Cost-Benefit analysis is done and using this project was determined to be quite useful.